Fundamentals of corporate finance - Brealey, Richard A. (McGraw-Hill/Irwin series in finance, insurance, and real estate., 2020)
'Fundamentals of Corporate Finance', by Brealey, Myers and Marcus, provides students with a solid framework of theory and application to use well after they complete the course. This author team is known for their outstanding research, teaching efforts, and world-renowned finance textbooks, so it's no surprise that they provide clear exposition of difficult material without sacrificing up-to-date, technically correct treatments.